Optimization of Ethanol Extract Preparation Gel Formula from the Combination of Lime Peel and Neem Leaves : Optimum Physical Properties and Antibacterial Activity - Rahmana, Andrea Yovva; Nurwaini, Setyo (Universitas Muhammadiyah Surakarta, 2024)
Lime peel (Citrus aurantifolia) and neem leaf (Azadirachta indica) have antibacterial properties, especially against Staphylococcus aureus. These two ingredients can be used to treat various skin problems caused by Staphylococcus aureus. This study aimed to determine the optimal ratio of 96% ethanol extract of lime peel and neem leaves to produce a gel formula with optimum physical properties and antibacterial activity. Physical properties tested were pH test, adhesion test, spreadability test, and viscosity test. Antibacterial activity was measured by inhibition zone diameter when tested by the well method. There were 8 gel formula with the various ratio of components of lime peel and neem leaves extracts, FI (8:2), FII (6.5:3.5), FIII (5:5), FIV (3.5:6.5), FV (2:8). The optimization method used was Simplex Lattice Design using the Design Expert 11 application (Trial). The optimum formula obtained from the Design Expert was verified and analyzed using the SPSS one-sample t-test with a 95% confidence level. The optimum formula of lime peel and neem leaves obtained were 8.00%:2.00% with a desirability value of 0.471. The one sample t-test showed that the results were not significantly different between the predicted and verified values.